اشكالية تنويع الاقتصاد الجزائري وإرساء النمو المستدام بين برامج الانعاش والرؤية الجديدة للنمو في آفاق 2030 - حبيب, كريمة; زقرير, عادل (University of eloued - جامعة الوادي, 2018)
تسعى هذه الورقة البحثية في المقام الأول: إلى تقييم وتحليل دور برامج الإنعاش الاقتصادي خلال الفترة (2001- 2014) في تحقيق إقلاع وتنويع الاقتصاد الجزائري . ومن أجل تحقيق هذا الهدف، سيتم عرض أهداف برامج دعم الإنعاش الاقتصادي، ومضمونها، ناهيك عن محاولة تقييم دور هذه البرامج في رفع معدلات النمو الاقتصادي. بعد ذلك، وفي المقام الثاني: يتم التطرق إلى النموذج الجديد للنمو الذي يجسد رؤية آفاق 2030، والتي تتمحور حول تنويع الاقتصاد الجزائري وإرساء النمو المستدام. وقد توصلت الدراسة إلى:  عدم قدرة برامج الانعاش الاقتصادي على تحقيق الاستدامة المطلوبة في نمو الاستثمارات وتحسين إنتاجيتها ورفع التوظيف في الاقتصاد، ومحدودية كبيرة في تنويع الاقتصاد الجزائري خارج المحروقات؛ وهذا ما أدى إلى:  تبني النموذج الجديد للنمو، والذي يمثل رؤية الجزائر في آفاق 2030 حول ضرورة التنويع الاقتصادي وارساء النمو المستدام. This paper seeks primarily to evaluate and analyze the role of economic recovery programs during the period (2001-2014) in achieving the takeoff and diversification of the Algerian economy. To achieve this goal, the objectives and content of economic recovery support programs will be presented, not to mention an attempt to assess the role of these programs in raising economic growth rates. Second, the new model of growth that embodies the Vision 2030, which focuses on diversification of the Algerian economy and sustainable growth, is addressed. The study concluded:  The inability of economic recovery programs to achieve the required sustainability in the growth of investments and improve productivity and raise employment in the economy, and a significant reduction in the diversification of the Algerian economy outside hydrocarbons, which led to:  Adopting the new model of growth, which represents Algeria's vision in the 2030 horizons on the need for economic diversification and sustainable growth.
مقال
Keywords: الاقتصاد الجزائري، الانعاش الاقتصادي، النمو الاقتصادي، النموذج الجديد للنمو. Algerian economy, economic recovery, economic growth, The new model of growth